PENGARUH PARTISIPASI ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN KEPERCAYAAN DAN KOMITMEN TUJUAN SEBAGI VARIABEL MODERATING (Studi Di Pemerintahan Kota Pekanbaru) - Hilfa Mora Marito Nst; Ria Nelly Sari; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aimed to examine the effect of budgetary participation and budget goal clarity on budgetary slack with trust and goal commitment as a moderating variable. This research is expected to help the government in order to improve the effectiveness of government budgets become increasingly better in the future.The sample used in this research is the echelon III and IV in Pekanbaru City Government. Data was collected through questionnaire survey method through. Of the 84 questionnaires distributed, the number of returnees is 75 questionnaire and a questionnaire that can be processed a number of 66 questionnaires. Data were analyzed using multiple regression (multiple regression) and moderate regression (Moderate Regression Analysis-MRA) with the help of a computer program SPSS version 17.0. The results showed that budgetary participation and budget goal clarity influence on budgetary slack. Participation budget and budget goal clarity moderated by the trust and goal commitment of purpose also affect the budgetary slack.Keywords: budgetary participation, budget goal clarity, trust, goal commitment and budgetary slack.